Pulsed cavitational ultrasound for non-invasive chordal cutting guided by real-time 3D echocardiography. (12th August 2016) - Villemain, Olivier; Kwiecinski, Wojciech; Bel, Alain; Robin, Justine; Bruneval, Patrick; Arnal, Bastien; Tanter, Mickael; Pernot, Mathieu; Messas, Emmanuel
Abstract: Aims: Basal chordae surgical section has been shown to be effective in reducing ischaemic mitral regurgitation (IMR). Achieving this section by non-invasive mean can considerably decrease the morbidity of this intervention on already infarcted myocardium. We investigated in vitro and in vivo the feasibility and safety of pulsed cavitational focused ultrasound (histotripsy) for non-invasive chordal cutting guided by real-time 3D echocardiography. Methods and results: Experiments were performed on 12 sheep hearts, 5 in vitro on explanted sheep hearts and 7 in vivo on beating sheep hearts. In vitro, the mitral valve (MV) apparatus including basal and marginal chordae was removed and fixed on a holder in a water tank. High-intensity ultrasound pulses were emitted from the therapeutic device (1-MHz focused transducer, pulses of 8 µs duration, peak negative pressure of 17 MPa, repetition frequency of 100 Hz), placed at a distance of 64 mm under 3D echocardiography guidance. In vivo, after sternotomy, the same therapeutic device was applied on the beating heart. We analysed MV coaptation and chordae by real-time 3D echocardiography before and after basal chordal cutting. After sacrifice, the MV apparatus were harvested for anatomical and histological post-mortem explorations to confirm the section of the chordae. In vitro, all chordae were completely cut after a mean procedure duration of 5.5 ± 2.5 min. The procedure duration was found to increase linearly with the chordae diameter. In vivo, the central basal chordae of the anterior leaflet were completely cut. The mean procedure duration was 20 ± 9 min (min = 14, max = 26). The sectioned chordae was visible on echocardiography, and MV coaptation remained normal with no significant mitral regurgitation. Anatomical and histological post-mortem explorations of the hearts confirmed the section of the chordae. Conclusions: Histotripsy guided by 3D echo achieved successfully to cut MV chordae in vitro and in vivo in beating heart. We hope that this technique will open the door in the near future to the non-invasive treatment of functional IMR.